Imaging of Scaphoid Fractures According to the New S3 Guidelines - Schmitt, R.; Rosenthal, H.; Deutsche Gesellschaft für Unfallchirurgie (DGU, Deutsche Gesellschaft für Orthopädie und Orthopädische Chirurgie (DGOOC), Deutsche Gesellschaft für Handchirurgie (DGH), Deutsche Gesellschaft für Plastische Rekonstruktive und Ästhetische Chirurgie (DGPRÄC), Deutsche Röntgengesellschaft (DRG), Deutsche Gesellschaft für Muskuloskelettale Radiologie (DGMSR); Participating working groups (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Up to 30 % of acute scaphoid fractures are missed in conventional radiography. CT and MRI should be early performed in the diagnostic workflow, when radiograms (dorsopalmar, lateral and Stecher’s views) are negative or inconclusive in fracture detection. Significance of CT is different from that of MRI: Sensitivity of CT imaging (85 to 95 %) is superior to conventional radiography (about 70 %), but inferior to MRI (almost 100 %). However, CT (specificity 95 to 100 %) is able to provide more detailed anatomic information of the fracture pattern when compared to MRI (specificity 80 to 90 %). Particularly, differentiation of bone contusion (“bone bruise”) and non-displaced fracture can be difficult in MRI. Thus, CT indication is not only given for fracture detection, but also for assessing the morphology in scaphoid fractures (localization, fragment dislocation, comminuted zones) and the fragment instability, too. MRI should be limited to equivocal trauma cases presenting pain in the snuff box, but with inconclusive CT findings. In CT and MRI of scaphoid fractures, image display must be aligned along the longitudinal extension of the scaphoid, either by acquiring or reformatting oblique-sagittal and oblique-coronal planes.Key points• Radiography can be limited to the dorsopalmar, lateral and Stecher’s views in scaphoid fractures.• In CT and MR imaging, the dedicated anatomy of the scaphoid has to be covered with oblique-sagittal and oblique-coronal images.• CT provides most detailed information of scaphoid fractures (localization, fragment dislocation and instability pattern). However, its capability in detecting non-displaced fractures is inferior to MRI.• All scaphoid fractures are seen in MRI. But differentiation of bone contusion (bone bruise) and a non-displaced fracture can be crucial.• This order is recommended in the diagnostic algorithm of scaphoid fractures: 1. radiography, 2. CT, and 3. MRI.Citation Format:• Schmitt R, Rosenthal H. Imaging of Scaphoid Fractures According to the New S3 Guidelines. Fortschr Röntgenstr 2016; 188: 459 – 469
Keywords: conventional radiography; CT; MR-imaging; trauma; scaphoid fracture